Metrics-based Analysis of Requirements for Object-Oriented systems: An empirical approach - Kanjilal, Ananya; Kanjilal, Goutam; Bhattacharya, Swapan (INFOCOMP Journal of Computer Science, 2008)
In an object-oriented environment, it is necessary to ensure that all the requirements are addressed in the design as well as implemented in a consistent manner in UML diagrams like sequence and class diagrams, which model the behavioral and structural aspects of the system. Metrics, which measures the degree of coverage of requirements and the extent of consistency between related models, will be a powerful tool for developers to have a quantitative feedback about the correctness of a system. We have proposed a new set of metrics namely Requirement Coverage Metrics (RCM) and Design Compliance Metrics (DCM) based on UML design models. RCM indicates the extent of coverage of requirements in design and highlights any missing requirements or inadequate coverage in design. It also helps in measuring progress of a project and thus helps in project management. DCM verifies whether the requirements that have been covered in design have been consistently realized in sequence and class diagrams or not. A case study has been considered and calculation of RCM and DCM has been done for illustration of our approach. We have also discussed implementation methodology using an XML based approach and in this paper we present implementation of a part of the metrics suite (DCM) for substantiation of our approach.